Determinants of profitability performance on microfinance in Malaysia – a study on SME Bank - Mohd Asyraf Thiru, Nurshafika (2018)
A microfinance institution (MFIs) was introduced in Malaysia in 1987 as one of the eradications of the poverty in the country. This project paper focused on selected bank specific factors give impact towards profitability performance of SME BANK in Malaysia. The purpose of this study is to examine the relationship and impacts of cost efficiency (CE), debt to equity (DE), cost per borrower (CPB) and write offs growth (WG) towards return on assets (ROA) of microfinance institutions in Malaysia. This study used semi-annually data collected from annual report of SME Bank in Malaysia over the period of June 2005 until December 2017. Ordinary Least Square (OLS) method is used in this study in order to do the empirical analysis using E-views. The finding indicated that positive insignificant relationship between CE, DE and CPB towards ROA of SME Bank in Malaysia. However, there one of variables which is WG has negative insignificant relationship towards ROA. This study enhanced the policy maker to used the cost efficiency wisely and also minimize the waste quantity as well as stakeholder to encourage political steadiness in view of the fact that microfinance institutions.